Action Potential Shortening and Impairment of Cardiac Function by Ablation of Slc26a6. (October 2017) - Sirish, Padmini; Ledford, Hannah A.; Timofeyev, Valeriy; Thai, Phung N.; Ren, Lu; Kim, Hyo Jeong; Park, Seojin; Lee, Jeong Han; Dai, Gu; Moshref, Maryam; Sihn, Choong-Ryoul; Chen, Wei Chun; et al.
Abstract : Background: Intracellular pH (pHi ) is critical to cardiac excitation and contraction; uncompensated changes in pHi impair cardiac function and trigger arrhythmia. Several ion transporters participate in cardiac pHi regulation. Our previous studies identified several isoforms of a solute carrier Slc26a6 to be highly expressed in cardiomyocytes. We show that Slc26a6 mediates electrogenic Cl − /HCO3 − exchange activities in cardiomyocytes, suggesting the potential role of Slc26a6 in regulation of not only pHi, but also cardiac excitability. Methods and Results: To test the mechanistic role of Slc26a6 in the heart, we took advantage of Slc26a6 knockout ( Slc26a6 −/ − ) mice using both in vivo and in vitro analyses. Consistent with our prediction of its electrogenic activities, ablation of Slc26a6 results in action potential shortening. There are reduced Ca 2+ transient and sarcoplasmic reticulum Ca 2+ load, together with decreased sarcomere shortening in Slc26a6 −/ − cardiomyocytes. These abnormalities translate into reduced fractional shortening and cardiac contractility at the in vivo level. Additionally, pHi is elevated in Slc26a6 −/ − cardiomyocytes with slower recovery kinetics from intracellular alkalization, consistent with the Cl − /HCO3 − exchange activities of Slc26a6. Moreover, Slc26a6 −/ − mice show evidence of sinus bradycardia and fragmented QRS complex, supporting the critical role of Slc26a6 in cardiac conduction system. Conclusions: Our study provides mechanistic insights into Slc26a6, a unique cardiac electrogenic Cl − /HCO3 − transporter in ventricular myocytes, linking the critical roles of Slc26a6 in regulation of pHi, excitability, and contractility. pHi is a critical regulator of other membrane and contractile proteins. Future studies are needed to investigate possible changes in these proteins in Slc26a6 −/ − mice. Abstract : Supplemental Digital Content is available in the text.